1
$\begingroup$

Now I have to solve this problem below:

Show that for every $t$, $$\dfrac{d}{dt}\text{Vol}(D_t)=\iiint_{D_t}\nabla\cdot\mathbf FdV$$

Here, for a region $D\subset\mathbb R^3$ and a vector field $\mathbf F$, $D_t$ is the image of a mapping $\Phi_t:D\rightarrow D_t\subset\mathbb R^3$, while $\Phi_t$ satisfies the condition: $$\dfrac{d}{dt}\Phi_t(X)=\mathbf F(\Phi_t(X)),\;\Phi_0(X)=X$$ $\text{Vol}(D_t)$ means the volume of $D_t$.

I think this should be related to the divergence theorem $\displaystyle\iint_{\partial D_t}\mathbf F\cdot\mathbf ndS=\iiint_{D_t}\nabla\cdot\mathbf FdV$, but the thing is that I did not learn the divergence theorem in 3 dimensions since I didn't learn about surface integrals. I also know for the fact that if a square matrix $A(t)$ is the identity matrix when $t=0$, then $\left.\dfrac{d}{dt}\right|_{t=0}\det A(t)=\text{trace}\left.\dfrac{d}{dt}\right|_{t=0}A(t)$. Also the definition of divergence I learned is if $\mathbf F=(f_1,f_2,f_3),\nabla\cdot\mathbf F=\dfrac{\partial f_1}{\partial x}+\dfrac{\partial f_2}{\partial y}+\dfrac{\partial f_3}{\partial z}$.

Any help would be appreciated.

$\endgroup$
2
$\begingroup$

By Reynolds transport theorem you have that $\frac{d}{dt}\left( \int_{\Omega(t)} \mathbf{f}\,dV\right) = \int_{\Omega(t)} \left( \frac{\partial \mathbf{f}}{\partial t} + \boldsymbol{\nabla} \mathbf{f}\cdot\mathbf{v} + \mathbf{f}\,\boldsymbol{\nabla} \cdot \mathbf{v}\right)\,dV$, so using $f=1, v=\dfrac{d}{dt}\Phi_t(X)=\mathbf F(\Phi_t(X)),\Omega(t)=D_t$ you get what you want.

$$\dfrac{d}{dt}\text{Vol}(D_t)=\frac{d}{dt}\left( \iiint_{D_T}dV\right) = \iiint_{D_T} \left( 0 + 0 +\boldsymbol{\nabla} \cdot \mathbf{\dfrac{d}{dt}\Phi_t(X)}\right)\,dV=\iiint_{D_t}\nabla\cdot\mathbf FdV$$


By Jacobi's formula we have $\frac{d}{dt} \det A =\mathrm{tr} ( \mathrm{adj}\ A \; \frac{dA}{dt})$ or in the equivalent form $\frac{d}{dt} \det A = \det A \; \mathrm{tr} \left(A^{-1} \frac{dA}{dt}\right)$ and for $\mathbf F$ we have that + $\frac{\mathbf dF}{dt}=F\nabla\varphi$ so putting everything together $$\frac{d}{dt} \det \mathbf F =\mathrm{tr}( \mathrm{adj}\ \mathbf F \; \frac{d\mathbf F}{dt})=\det \mathbf F \; \mathrm{tr}(\mathbf F^{-1} \frac{d\mathbf F}{dt})=\det \mathbf F \; \mathrm{tr}(\nabla\varphi)=\det \mathbf F \; \nabla\varphi$$

and we recover $\frac{d}{dt} \det \mathbf F =\det \mathbf F \; \nabla\varphi$ that is how it is used in the first link.

Hope it helps

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.